A. \(S = \frac{{11\pi }}{6}\)
B. \(S = 4\pi \)
C. \(S = 5\pi \)
D. \(S = \frac{{7\pi }}{6}\)
B
\(\left( {2\cos 2x + 5} \right)\left( {{{\sin }^4} - {{\cos }^4}x} \right) + 3 = 0 \Leftrightarrow \left( {2\cos 2x + 5} \right)\left( {{{\sin }^2}x - {{\cos }^2}x} \right) + 3 = 0\)
\( \Leftrightarrow - \left( {2\cos 2x + 5} \right)\cos 2x + 3 = 0 \Leftrightarrow - 2{\cos ^2}\left( {2x} \right) - 5\cos 2x + 3 = 0 \Leftrightarrow \cos 2x = \frac{1}{2}\)
\(\cos 2x = \frac{1}{2} \Leftrightarrow x = \pm \frac{\pi }{6} + k\pi \left( {k \in \mathbb{Z}} \right) \Rightarrow x \in \left\{ {\frac{\pi }{6};\frac{{5\pi }}{6};\frac{{7\pi }}{6};\frac{{11\pi }}{6}} \right\}\)
Do đó \(S = \frac{\pi }{6} + \frac{{5\pi }}{6} + \frac{{7\pi }}{6} + \frac{{11\pi }}{6} = 4\pi \)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247